2022
DOI: 10.22270/jddt.v12i4.5458
|View full text |Cite
|
Sign up to set email alerts
|

Holarrhena antidysenterica in Inflammatory Bowel Disease: a potential review

Abstract: Holarrhena antidysenterica belongs to the Apocynaceae family and is generally known as kurchi in Hindi. It is a small deciduous tree found in arid woods throughout the world including India. H. Antidysenterica is commonly used in Indian traditional medicine to treat Inflammatory Bowel disease, dysentery, diarrhoea and worms in the intestines.  Plant parts like bark are useful in antimicrobial, anti-inflammatory and analgesic treatments, amoebiasis, chronic bronchitis, boils, and ulcers. The Phytoconstituents  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The flavonoids and phenolic components in Holarrhena pubescens aqueous and methanolic bark extract showed high antioxidant activity [ 25 ] H . pubescens alkaloids were shown to be useful in treating acute dysentery, inflammatory bowel illness, diarrhoea, and, worm infections in the gut [ 28 ]. It is also reported that H .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The flavonoids and phenolic components in Holarrhena pubescens aqueous and methanolic bark extract showed high antioxidant activity [ 25 ] H . pubescens alkaloids were shown to be useful in treating acute dysentery, inflammatory bowel illness, diarrhoea, and, worm infections in the gut [ 28 ]. It is also reported that H .…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that H . pubescens , may be helpful to an extent, in treating Amoebiasis [ 29 ] and this plant also has anti-diabetic, anti-amnesic and anti-inflammatory property [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flavonoids and phenolic compounds of aqueous and methanolic bark extract of Holarrhena pubescens showed strong antioxidant property (Bhusal 2014). All the alkaloids of H. pubescens were found effective in treating acute dysentery, inflammatory bowel disease, diarrhoea and worm infections in the intestine (Bala et al 2022). It is also reported that Kutaja, may be helpful to an extent, in treating Amoebiasis (Singh 1986) and this plant also has anti-diabetic, anti-amnesic and anti-inflammatory property (Bala et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Kurchi is the name given to the stem bark of this plant, which contains astringent, antidiarrheal, antidysenteric, anti-anthelmintic, stomachic, febrifugal, digestive, and tonic characteristics. Medicinal properties of H. pubescens summerised in table 1 [6] .…”
Section: Introductionmentioning
confidence: 99%